Video Streaming to Empowered Video Walls - Sven Ubik; Jiri Melnikov; Zdeňek Trávníček (International Journal of Electronics and Telecommunications, 2018)
Video walls are useful to display large size video content. Empowered video walls combine display functionality with computing power. Such video walls can display large scientific visualizations. If they can also display high-resolution video streamed over a network, they could enable distance collaboration over scientific data. We proposed several methods of network streaming of highresolution video content to a major type of empowered video walls, which is the SAGE2 system. For all methods, we evaluated their performance and discussed their scalability and properties. The results should be applicable to other web-based empowered video walls as well.